2022
DOI: 10.1097/ncc.0000000000001094
|View full text |Cite
|
Sign up to set email alerts
|

Coproducing and Implementing Person-Centered Key Performance Indicators in Ambulatory Cancer Nursing

Abstract: BackgroundPolicy advocates person-centered healthcare for people living with cancer. Although nurses and patients alike recognize that a good care experience cannot be measured solely by clinical outcomes, the difficulty in finding indicators that measure the delivery of effective person-centered care remains a challenge.ObjectiveThe aim of this study was to explore the impact of a coproduced implementation project using the person-centered nursing key performance indicators to support the development of perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The CONTACT‐PCCQ can also be used in the context of improvement projects, for example, the development, implementation and evaluation of a care pathway or educational intervention. As shown in the study of Lynch and McCance (2022), the implementation of relevant and appropriate key performance indicators (KPI) can provide valuable feedback to HCPs and contribute to more patient‐centred practices in ambulatory cancer care (Lynch & McCance, 2022). However, data collection can be time consuming and challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CONTACT‐PCCQ can also be used in the context of improvement projects, for example, the development, implementation and evaluation of a care pathway or educational intervention. As shown in the study of Lynch and McCance (2022), the implementation of relevant and appropriate key performance indicators (KPI) can provide valuable feedback to HCPs and contribute to more patient‐centred practices in ambulatory cancer care (Lynch & McCance, 2022). However, data collection can be time consuming and challenging.…”
Section: Discussionmentioning
confidence: 99%
“…As these medicines are often taken on a long-term basis, the situation of cancer patients treated with OACD is comparable to that of patients with chronic conditions for whom achieving an adequate level of self-management is essential. In chronic conditions, patient education and counselling are key aspects in the care process and are crucial to ensure effective patient selfmanagement (Kinnaer, De Coster, et al, 2019;Legido-Quigley et al, 2013). Many authors have stressed the importance of an individualised approach for patients taking OACD (Kav et al, 2010;Rittenberg, 2012) and showed that, for example, tailored educational interventions may promote adherence (Arthurs et al, 2015;Kavookjian & Wittayanukorn, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These KPIs and accompanying measurement framework were developed and tested internationally across a range of specialities (Lynch & McCance, 2022;McCance et al, 2012, 2015, McCance, Dickson, et al, 2020Wilson et al, 2021). The measurement framework includes qualitative and quantitative data.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…One response to this identified gap was the development of eight person‐centred nursing key performance indicators (KPIs) (see Table 1) by McCance et al (2012). These KPIs and accompanying measurement framework were developed and tested internationally across a range of specialities (Lynch & McCance, 2022; McCance et al, 2012, 2015, 2016, McCance, Dickson, et al, 2020; McCance, Lynch, et al, 2020; Wilson et al, 2021). The measurement framework includes qualitative and quantitative data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, KPI 5 (Time spent by nurses with the patient) is informed by survey data, observations, and the patient stories. The KPIs and measurement framework has been evaluated in a range of contexts [5][6][7]. This work has been underpinned by the MRC guidelines for the development, evaluation and implementation of complex interventions [8].…”
Section: Introductionmentioning
confidence: 99%